Airport passenger technology readiness and self-service bag drop technology adoption at South African Airports - Atcha, Mohammed Haaroon (My University, 2020)
Self-service bag drops (SSBDs) have received considerable attention over the last few years as they offer potential savings and efficiency gains for airports and airlines alike; however, little is known about passengers’ readiness to adopt such self-service technologies (SSTs) The objective of this research was to determine passengers’ Technology Readiness (TR) and SSBD adoption at South African airports using the Technology Readiness and Acceptance Model (TRAM). For user adoption testing to be viable, the associated model of user motivation must be valid. In order to validate the utility of the TRAM framework for this study, the following research steps were conducted: (1) The most widely cited, empirically replicated, and accepted model of human behaviour, the technology acceptance model (TAM), was the paradigm from which the TRAM was conceived; (2) Shortcomings identified by users of the TAM were mitigated by the introduction of the TR construct to form the TRAM; and (3) Published literature was reviewed to demonstrate that empirical support exists for the TRAM. Partial least squares structural equation modelling (PLS-SEM) was used to test the 10 linkages and two potential moderating effects in the TRAM framework. Twelve hypotheses were tested, of which 10 were accepted. The two hypotheses that were rejected were the potential moderating effects of TR. Six constructs (i.e., Technology Readiness Index [TRI], perceived ease of use [PEOU], perceived usefulness [PU], attitude, behavioural intention, and adoption) were tested, providing valuable information for airports and airlines in deciding to implement SSBDs. The research findings provide evidence that TRAM is a robust model that can be used to predict human behaviour as it relates to the adoption of self-service technologies (SSTs) in general, and SSBDs at South African airports in particular
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science in Engineering, 2020